Establishment and application of dual rpa-basic and rpa-lfd detection method for pasteurella multocida and actinobacillus pleuropneumoniae - Jingjing LI; Xiaobing WEI; Shuang LI; Mingcheng LIU; Qianlei ZHU; Kexin WANG; Lei WANG; Yingying CAO; Meinan CHANG; Chunling ZHU; Zhanwei TENG; Xuehan LIU; et al. (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Based on recombinase polymerase amplification (RPA) detection technology (combined with (lateral flow dipstick, LFD)), it is aimed to establish a dual recombinase polymerase amplification method for the rapid identification of Pasteurella multocida (Pm) and Actinobacillus pleuropneumoniae (APP). The conserved fragments of Pm kmt1 gene and APP ApxIV gene were selected for the amplification of target fragments. Eight pairs of primers for Pm and APP, and one probe for KMT1Pn and APP323Pn were designed. A single RPA-Basic primer screening test was performed. The reaction time and temperature of double RPA were optimized. The optimal primers and probe matching systems of dual RPA-LFD were explored. Dual RPA sensitivity and specificity tests were performed. The method was used to detect 60 clinical samples. The results of the primer screening test showed that the primers had the strongest specificity and the highest amplification efficiency for ApxIV2698F/ApxIV3020R and KMT1F/KMT1R. The method had the best amplification efficiency at a reaction temperature of 37ºC and a reaction time of 35 min. The optimal primer ratio of KMT1F/KMT1R and ApxIV2698F/ ApxIV3020R was 2 μL : 1.5 μL, and the optimal probe ratio of KMT1Pn and APP323Pn was 0.6 μL : 0.4 μL. The minimum detection limit of dual RPA-Basic and RPA-LFD sensitivity test was 10-6 ng/μL. The specific test results showed no cross-reaction with enteropathogenic Escherichia coli, Salmonella, Glaesserella parasuis, Staphylococcus aureus, Streptococcus suis, Aeromonas hydrophila. Using 60 clinical samples of suspected Pm and/or APP infection to evaluate the detection system, the detection rate of dual RPA-Basic and RPA-LFD is higher than that of PCR, indicating that they have strong practicability. This study successfully established a dual RPA-Basic and RPA-LFD detection method for Pm and APP, which can be used for the rapid differential diagnosis of Pm and APP mixed infection in clinical.